ORANG MUDA DAN PENGEMBANGAN SOSIAL EKONOMI MENURUT PAUS FRANSISKUS - Alphonsus Boedi Prasetijo (Bahasa Indonesia, 2018)
Pope Francis wrote a forward in DOCAT, an outstanding social justice resource for today’s young people. DOCAT is revealing the secret to young people around the world with the Church’s beautiful social teachings. DOCAT helps young people to know and to live Catholic Social Teaching. It’s an inspiring, practical follow up to YOUCAT, the hugely popular Youth Catechism, based on the Catechism of the Catholic Church. Young people can learn on economic and social development based on the golden passage of the Gospel according to St. Matthew chapter 25:40 and the inspiration of Mother Theresa’s life. Pope Francis also highlights on economic and social life in Apostolic Exhortation on Proclamation of the Gospel in Today’s World, Evangelii Gaudium (The Joy of the Gospel).